MORAL VALUES AND INTRINSIC ELEMENTS IN CRAZY RICH ASIANS NOVEL - Weliza Agustina; Baginda Simaibang; Mulyadi Mulyadi (Esteem Journal of English Education Study Programme, 2022)
The main of this study was discovering intrinsic elements and moral values in Crazy Rich Asians Novel, besides the theoretical implications of ELT strategy. The qualitative study method was used in this study. The data were obtained from the novel's words, phrases, sentences, and utterances. Data were collected in three ways: documentation, interviews, and book reviews. Data analysis comprise specifying, reducing, itemizing, framing data and making conclusion. The novel's intrinsic elements included theme, characters, plot, setting, and subject matter; moral values in the novel included four aspects: commitment to something greater than oneself, respect for oneself, but with humility, self-control, acceptance of personal responsibility, respect for others and concern for their well-being, concern for other living things as well as the environment. The most dominant moral value was respect for others and concern for their well-being. This study was not previously conducted in other studies because it investigated more recent information about the exploration of moral values and intrinsic elements in Crazy Rich Asians Novel. This study encouraged English educators to use novels as a medium for learning literature in ELT strategy and the result of this study can be used as a resource for English educators and L2 students.